Research note the effect of physical attractiveness on teacher expectations - Clifford, Margaret M.; Walster, Elaine (1973)
Rosenthal and Jacobson found that a teacher's expectations about a child's behavior strongly influence his actual behavior. Generally, teachers form their first impression of children, and thus develop their expectations for them, from two sources of information-the children's school record and their physical appearance. In this experiment, teachers were given objective information, presumably about a child scholastic and social potential, accompanied by a photograph of an attractive or an unattractive boy or girl. It was found that the child's attractiveness was significantly associated with the teacher's expectations about how intelligent the child was, how interested in education his parents were, how he was likely to progress in school, and how popular he would be with his peer.
Photocopy.
Includes bibliographical references (pages 256-258)
Keywords: Expectation (Psychology) in children; Teachers -- Training of